2019
DOI: 10.2147/nrr.s207497
|View full text |Cite
|
Sign up to set email alerts
|

<p>Health literacy and informed consent for clinical trials: a systematic review and implications for nurses</p>

Abstract: The informed consent process for consideration of clinical trials is a complex process that requires the understanding of the potential trial risk, benefits, and alternatives of treatment. The aim of this systematic review was to explore the available literature related to health literacy and the informed consent process for clinical trials. Articles were included if they focused on health literacy and patient comprehension of informed consent, had perceptions related to the informed consent process, or assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Prognostication is challenging. However, diabetes is known to reduce life expectancy compared to the general population and there are some well-described general indicators of declining life expectancy (30). In addition, our literature review for the current study revealed seven main diabetes-related factors associated with reduced life expectancy: duration of diabetes, glycaemia, comorbid load/ geriatric syndromes, severe hypoglycaemia, lower limb and foot disease, polypharmacy and comorbid depression (11).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Prognostication is challenging. However, diabetes is known to reduce life expectancy compared to the general population and there are some well-described general indicators of declining life expectancy (30). In addition, our literature review for the current study revealed seven main diabetes-related factors associated with reduced life expectancy: duration of diabetes, glycaemia, comorbid load/ geriatric syndromes, severe hypoglycaemia, lower limb and foot disease, polypharmacy and comorbid depression (11).…”
Section: Discussionmentioning
confidence: 84%
“…Mirroring may also contain elements of health literacy. Health literacy is important to quality care and can affect patients' decisions and actions (30). However, clinician health literacy is rarely considered and can also have a profound effect on outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A patient’s health literacy is an important component of high-quality care that can influence on clinical decisions and actions of patients and providers. 25 Adequate health literacy and a better understanding of health education are highly correlated. 20 Those patients having low health literacy reported less participation in their care with the clinician, which in turn results in poorer health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…answering multi-choice questions, notating the information, or researchers using techniques such as the teach-back method to ensure explanations are effective) and build a rapport with the researcher. 52,85,89 Meanwhile, researchers must promote transparency by declaring their conflict of interest; empathy with participants' welfare against meeting enrolment goals. 84 Assessing health literacy and patient comprehension.…”
Section: Potential Strategies To Improve Informed Consent In Haemophilia Gene Therapymentioning
confidence: 99%